Don’t stop me now, I’m having such a good time! Czechoslovakian Wolfdogs renovate the motivation to play with a bow - Veronica MAGLIERI; Anna ZANOLI; Fosca MASTRANDREA; Elisabetta PALAGI (Current Zoology, 2023)
Dogs engage in play behavior at every age and the play bow is their most iconic playful posture. However, the function of this posture is still under debate. Here, we selected the Czechoslovakian Wolfdog (CWD) as a model breed to clarify the function of the play bow. We analyzed frame-byframe 118 sessions of 24 subjects and recorded 76 play bow events. We found that all the play bows were performed in the visual field of the playmate suggesting that the sender takes into account the attentional state of the receiver when releasing the signal. By drawing survival curves and using log-rank test we found that play bow was mainly performed during a short pause in an ongoing session and that its performance triggered the playmate’s reaction again. These findings show that play bow functions in restoring the partner motivation to play. Finally, by using a sequential analysis and a generalized mixed model, we found no evidence supporting the metacommunicative function of the play bow. The signal did not necessarily precede a contact offensive behavior (e.g., play biting and play pushing) and it was not affected by the level of asymmetry of the play session. In conclusion, in CWDs play bow can be considered a visual signal useful to maintain the motivation to play in the receiver. Therefore, we suggest that the mismatched number of play bows emitted by the 2 players in a given session can be predictive of their different motivations to play